Pengaruh Model Jigsaw Berbantuan Media Digital Ular Tangga Terhadap Minat Belajar Matematika Kelas III Sekolah Dasar - Utameiy, Icha; Supriatna, Irfan; Amaliyah, Yuli (Universitas Bengkulu, 2025)
This study aims to determine how the Jigsaw learning model assisted by digital media tables of snakes and ladders affects students' learning interest in mathematics learning in grade III at SDN Kota Bengkulu. This study is a quantitative study using a quasi-experimental method. The type of research design applied is a Control Group Pretest-Posttest Matching Only design. This study involved grade III students of SDN 38 Kota Bengkulu. Meanwhile, the sample consisted of grade IIIB students of SDN 38 Kota Bengkulu, which served as the experimental class, and grade IIIA students of SDN 38 Kota Bengkulu, which served as the control class. This sample was taken through a random sampling group. Non-test tools were used in measuring learning interest using initial and final questionnaires. The results of the hypothesis test in the experimental class showed that the calculated t value, assuming equal differences, was 4.675, with a two-tailed sigma value of 0.027, and a distribution value of 1.967. Therefore, the calculated t value was greater than the t value (4.308 is greater than 1.697), and the two-tailed sigma value of 0.037 was less than 0.05. These data indicate that the difference in average learning interest between the experimental and control classes was due to the way each class was treated. Therefore, it can be concluded that the Jigsaw learning model, assisted by digital media like Snakes and Ladders, has an impact on students' learning interest in mathematics in third grade at SDN 38, Bengkulu City.